Epidemiological relationships among penicillin non-susceptible Streptococcus pneumoniae strains recovered in the Czech Republic - Žemličková, Helena; Melter, Oto; Urbášková, Pavla (Journal of medical microbiology, 2006)
Since 1986, penicillin non-susceptible pneumococci (PNSP) have been found in the Czech Republic. As documented by a nationwide study, the proportion of invasive strains with reduced susceptibility to penicillin has fluctuated around 5 % in the past decade. Although the level of resistance to penicillin remains stable, the contribution of different capsular serotypes among the PNSP population varies. Whereas serotype 19A was predominantly associated with penicillin resistance until 1997, serotype 9V became most common among PNSP strains in 1998. In a collection of PNSP strains (n=225) isolated from 2000 to 2002, the most frequent serotype was 9V (n=91, 40.4 %), followed by 19F (n=30, 13.3 %) and 14 (n=25, 11.5 %). PFGE and multilocus sequence typing were used to characterize a set of PNSP of the currently predominant serotypes 9V (n=42), 14 (n=15) and 19F (n=14). The Spain(9V)-3 clone [sequence type (ST) 156] was responsible for a large proportion (100 % of serotype 9V strains, n=42; 93.3 % of serotype 14 strains, n=14) of the analysed strains. A representative of the Taiwan(19F)-14 clone (ST 236) was also recovered in the Czech Republic (a single isolate of serotype 19F). These findings confirm the spread of the major penicillin-resistant clones in the Czech Republic.
Keywords: antibakteriální látky; pneumokokové infekce; Penicillin Resistance; Anti-Bacterial Agents; Penicillins; Česká republika; lidé; rezistence na penicilin; Pneumococcal Infections; Streptococcus pneumoniae; Humans; peniciliny; Czech Republic